Transactional sex among women in Sub-Saharan Africa: A systematic review and meta-analysis. - Gedefaye Nibret Mihretie; Bekalu Getnet Kassa; Alemu Degu Ayele; Tewachew Muche Liyeh; Habtamu Gebrehana Belay; Agernesh Dereje Miskr; Binyam Minuye; Melkalem Mamuye Azanaw; Mulugeta Dile Worke (PLoS ONE, 2023)
Introduction Transactional sex is casual sex between two people to receive material incentives in exchange for sexual favors. Transactional sex is associated with negative consequences, which increase the risk of sexually transmitted diseases, including HIV/AIDS, unintended pregnancy, unsafe abortion, and physiological trauma. In Sub-Saharan Africa, several primary studies have been conducted in various countries to examine the prevalence and associated factors of transactional sex among women. These studies had great discrepancies and inconsistent results. Hence, this systematic review and meta-analysis aimed to synthesize the pooled prevalence of the practice of transactional sex among women and its associated factors in Sub-Saharan Africa. Method Data source: PubMed, Google Scholar, HINARI, the Cochrane Library, and grey literature were searched from March 6 to April 24, 2022, and included studies conducted from 2000 to 2022. The pooled prevalence of transactional sex and associated factors was estimated using Random Effect Model. Stata (version 16.0) was used to analyze the data. The I-squared statistic, a funnel plot, and Egger's test were used to check for heterogeneity and publication bias, respectively. A subgroup analysis was done based on the study years, source of data, sample sizes, and geographical location. Results The pooled prevalence of transactional sex among women in Sub-Saharan Africa was 12.55% (9.59%-15.52%). Early sexual debut (OR = 2.58, 95% CI: 1.56, 4.27), substance abuse (OR = 4.62, 95% CI: 2.62, 8.08), history of sexual experience (OR = 4.87, 95% CI: 2.37, 10.02), physical violence abuse (OR = 6.70, 95% CI: 3.32, 13.53), orphanhood (OR = 2.10, 95% CI: 1.27, 3.47), and sexual violence abuse (OR = 3.76, 95% CI: 1.08, 13.05) were significantly associated with transactional sex. Conclusion The prevalence of transactional sex among women in sub-Saharan Africa was high. Alcohol consumption, substance abuse, early sex debuts, having a history of sexual experiences, physical violence, and sexual violence increased the practice of transactional sex.